2012
DOI: 10.5815/ijisa.2012.09.10
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Induced Fuzzy Cognitive Maps to the Problems Faced by the Power Loom Workers

Abstract: -The Indian text ile industry has a significant presence in the economy as well as in the international text ile economy. In this research Paper we study the socio economic problems faced by power loo m workers in Avinashi in Tamilnadu, India, using Induced Fuzzy Cognitive Maps (IFCMs). We have interviewed 50 households in the study area using a linguistic questionnaire. As the problems faced by them at la rge, involved so much of feelings and uncertainties. We felt it to fit to use fu zzy theory in general an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Narayanamoorthy et al, [9] obtained maximum age group of endosulfan pesticide victims in Kerela using fuzzy combined effect time dependent-data-matrix. Kokila [10] worked on student's information gathering attitude by applying fuzzy matrix combined effect time dependent data matrix. Jon Arockiaraj and Murali [11] reported that the using fuzzy matrix analysis of seasonal fishing in Cuddalore.…”
Section: Introductionmentioning
confidence: 99%
“…Narayanamoorthy et al, [9] obtained maximum age group of endosulfan pesticide victims in Kerela using fuzzy combined effect time dependent-data-matrix. Kokila [10] worked on student's information gathering attitude by applying fuzzy matrix combined effect time dependent data matrix. Jon Arockiaraj and Murali [11] reported that the using fuzzy matrix analysis of seasonal fishing in Cuddalore.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Narayanamoorthy et al [12] used a fuzzy combined effect time dependent data matrix to estimate the maximum age group of endosulfan pesticide victims in Kerela. Kokila [13] used a fuzzy matrix combined effect time dependent data matrix to study student's information gathering attitudes. Jon Arockiaraj and Murali [14] reported that a fuzzy matrix analysis was used to analyze seasonal fishing in Cuddalore.…”
Section: Introductionmentioning
confidence: 99%
“…Narayanamoorthy [11] estimated the maximum age group of silk weaver as bounded labours using fuzzy combined effect time dependent data matrix. Narayanamoorthy et al, [12] obtained maximum age group of endosulfan pesticide victims in Kerela using fuzzy combined effect time dependent-data-matrix. Kokila [13] worked on student's information gathering attitude by applying fuzzy matrix combined effect time dependent data matrix.…”
Section: Introductionmentioning
confidence: 99%